Percepcion de la calidad de servicio en la escuela academico profesional de educacion secundaria con mencion en idiomas 2013-ii, unt; respecto al modelo coneau - Cuba Campos, David Jonatan (2014)
This research aims to understand the perception of service quality in Vocational Secondary School Scholar majoring Languages , National University of Trujillo, in the 2013 -II semester , according CONEAU 2010 model , by students of this school. Also, it will have as main objective to determine how they are indicators of service quality in school majoring in Secondary Education Languages from the results of this research, which will contribute to improving their quality of education. The population will be students majoring in Secondary Education II Languages 2013, of which a sample is given by stratified sampling. The information will be collected by questionnaire, with reference to developed and validated by the Board of Assessment, Accreditation and Quality Assurance of the Assessment of Higher Education University (CONEAU ) survey.